Management control system, leadership and gender ideology: A study of an Indonesian construction company. Issue 4 (7th November 2016) - Efferin, Sujoko; Frisko, Dianne; Hartanto, Meliana
Abstract : Purpose: The purpose of this paper is to reveal the relations between management control system (MCS), leadership style and gender ideology. It investigates how a female leader's gendered personal values are formed, translated, produced, and reproduced in her leadership style, the subsequent MCS and organisational life. Design/methodology/approach: This is an interpretive case study that uses the anthropological lens of emic and etic views. The emic view is derived from the interpretation of the company's subjects. The etic view refers to the interpretation of outsiders (the researchers and previous literatures). The combination of these two views enables an in-depth understanding of the case. Interviews, observation and documentary analysis were used to collect the data. Findings: In a gendered society, a female leader will gain full respect if she demonstrates leadership behaviours that fit her subordinates' gendered expectations. The leader's and followers' common gendered cultural background will result in leadership and followership that support each other. Gendered leadership produces gendered MCS. Gendered MCS is based on gendered cultural values that direct the behaviour of organisational members to focus on certain competencies based on a single gender perspective. In turn, the gendered MCS sustains and reinforces the gendered leadership. Research limitations/implications: The study does not focus on the potential value of including feminine measures in MCS. In the future, MCS literatures need to explore the strategic advantages of introducing measures into the system in order to develop feminine competencies in organisation. Furthermore, the processes by which MCS reinforces gendered practices in a society are not explored in the study. Therefore, another important next step is to examine the patterns of the reinforcement processes and their magnitude in strengthening the biases beyond organisational boundaries (e.g. in professional and industrial practices). Practical implications: This study encourages leaders to consider the use of masculine and feminine characters in MCS to increase organisational effectiveness, build a more humane organisational atmosphere, establish organisational cohesion and harmonise different personal aspirations. Originality/value: MCS literatures tend to hide gender bias in the system. This study offers insight on how MCS translates, produces and reproduces societal gendered practices in organisational life.